SINTESIS DAN KARAKTERISASI FT-IR MATERIAL GIANT DIELECTRIC CCTO DENGAN METODE REAKSI PADATAN - Siska Febriana; Kamsul Abraha (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Synthesis of giant dielectric material CaCu3Ti4O12, commonly called CCTO, using a solid-state reaction method has been done. The technique includes of mixing, compacting and heating such as calcination and sintering. The three types of starting powders : CaCO3, CuO and TiO2 were mixed then calcinated at 1100 and sintered for different temperatures at 500 , 700 and 900 . The sintered powders were characterized by X-ray diffraction (XRD) for investigate the cristalinity phase, FT-IR spectroscopy and grain size measurement. X-ray diffraction results show that CCTO synthesized with sintering treatment give material a better crystallinity than without using sintering treatment. FT-IR characteristic spectra show the main absorption at wavenumber 447,49 for 500 , 700 and 900 sintered powder that indicate the vibrations of vTi-O-Ti type. Furthermore, the vTi-O type vibrations appear at wavenumber 509,21 and 555,5 ; 516,92 and 570,93 ; 524,64 and 578,64 for 500 , 700 and 900 sintered powder respectively. However, the results of grain size calculation point out that the grain size increases with increasing sintering temperature. Keywords : Solid-state reaction, X-ray diffraction, FT-IR spectroscopy.